Challenges and opportunities on Islamic inheritance distribution in Indonesia - MHI1Dian Berkah; Sawarjuwono, Tjiptohadi; M.Ag, Abd. Hadi (Opción, 2019)
This paper seeks to identify the challenges and opportunities for inheritance distribution in Indonesia by using a library-based study method which is a kind of qualitative research approach. As a result, the potential funding sourced from the estate’s people would be the greatest opportunity for Indonesia as an income of the people beside zakat funds and waqf. In conclusion, identification of the challenges and opportunities in inheritance distribution may benefit the religion court in completing inheritance distribution